Presenting a model for the establishment and maintenance of expert human resources in the government organizations of Sistan and Baluchestan province - Majid Reza Dahmardeh; Vahid pourshahabi; Amin Reza Kamalian; Habibollah Salaerzehi (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research is to identify indicators and effective factors in the maintenance of expert human resources in deprived and less developed areas and their ranking, as well as to draw a model of maintenance with an ecological approach, centered on the government organizations of Sistan and Baluchistan province, which is applicable in terms of purpose; and Regarding the implementation method, it is survey based on structural equation modeling. The statistical population included 181 managers and experts of government organizations in Sistan and Baluchistan province, from which 123 people were selected as a sample using Cochran's method. The data of this research was collected through a questionnaire created by the researcher, and validity and construct validity were used in order to evaluate the validity of the final questionnaire. Structural equation technique and Smartpls software were used to analyze the data. The results show that in this research, the dimensions of maintaining expert human resources include: behavioral, structural, contextual, and normative/attitudinal factors; and 31 components, based on the output of structural equation analysis and path analysis technique, the path coefficient of behavioral factors is 0.901, structural factors 0.886, contextual 0.821, and normative/attitudinal 0.840, in which the behavioral factors have the greatest impact and the job satisfaction component with a significant number obtained from the T-test equals 24.004 and the path coefficient 0.901 has played the greatest role in maintaining expert human resources in the government organizations of Sistan and Baluchistan provinceExtended abstractIntroductionHuman capital is considered the most complex and valuable capital in any organization, which plays the main role in realizing the organization's goals. If we carefully study the national wealth of a society, we come across two types of capital resources: material capital and human capital, meanwhile, it is the existence of trained and expert human capital that uses material capital, and its lack and deficiency is the reason for the loss and stagnation of the national capital and the decline of production and reproduction (Armestrang, 2018). For this purpose, most of the organizations consider the issue of maintaining the human resources of the organization as important and fundamental, and plan for it and spend a lot of money on it. One of the basic missions of human resources management of organizations is to maintain capable employees. Because maintenance measures are complementary to other human resource management measures and processes; even if the recruitment, selection, appointment and improvement operations are done properly, the results of management actions will not be very impressive without paying enough attention to maintenance. In many businesses, employee retention has become a major concern. The longer a person stays in the organization, the more skills he acquires; so ideally, employees should stay for a long time so that the organization achieves consistent success (Chawla. 2021). Therefore, maintaining human resources and preventing the loss of workforce in leading organizations has become one of the most important concerns of human resource management. In fact, leaving a job is a kind of work challenge that is associated with a decrease in the amount of physical and mental energy in employees. Today, leaving a job has attracted a lot of attention from researchers and organizational leaders, which is mainly related to important organizational and individual consequences such as job performance, organizational behavior, job attitudes, and negative psychological consequences. In the event of a drop in specialized forces, the movement of the organization will be affected and it will appear as a problem for the managers of the organizations who seek to preserve, maintain, improve and improve the productivity of their human resources, which can bring irreparable consequences for the organization (Khalili Tabar et al., 2020).The basis of every organization is development and movement, and this is possible through specialized and efficient human resources. Currently, attracting and maintaining specialized human resources, especially in less developed and deprived areas, is one of the most important strategies in the field of strategic human resources management, and on the other hand, it is one of the most serious problems of organizations in the modern era, which today, in completely changing conditions governing organizations, The increase in competition and the necessity of its effectiveness in such conditions reveals their need for a valuable generation of employees who are referred to as organizational soldiers, the national wealth of the land, and drivers of development. Therefore, the strategic and economic advantage in the future will be given to organizations that attract, cultivate and maintain this best and brightest human capital better than others. Undoubtedly, this will be an important characteristic of effective organizations; therefore, the purpose of this research is to design a model for the feasibility and establishment of maintaining expert human resources in government organizations of Sistan and Baluchistan province.Theoretical literatureHuman resource retention: The term human resource retention can be defined as an effort to create and improve an environment over a long period of time that continues to encourage employees to work while implementing policies and practices that suit their various needs.Talent management: Talent management is the strategic management of the flow of talents in the organization, and its goal is to create an available source of talent to match the right people with the right jobs at the right time based on the strategic goals of the business. Also, talent management can be defined as the management of the supply, demand and flow of talented people through the engine of human capital (Roknabadi & Adibzadeh, 2023).Suman (2024) in a research titled Employee Retirement and Planning for Retention in the Public and private Sectors in the United Kingdom, using a mixed method and combining quantitative and qualitative techniques, investigated the correlation between employee interaction and their retention. The data showed that employee turnover rates varied significantly across UK industries.Roknabadi & Adibzadeh (2023), in a research titled identifying and prioritizing the factors affecting human resources maintenance in Islamic Azad University, came to the conclusion that maintaining expert staff in Islamic Azad University first requires attracting efficient, committed and specialized staff.Research methodologyThe current research is applicable in terms of its purpose, and survey in terms of the execution method, and is based on structural equation modeling. The statistical population included 181 managers and experts of government organizations in Sistan and Baluchistan province, from which 123 people were selected as a sample using Cochran's method. The data of this research was collected through a researcher-made questionnaire.In order to analyze the data, the structural equation modeling method, the path analysis technique, and the Smartpls software were used to determine the factor load of the manifest and hidden variables. In order to conduct the research, the final questionnaire was provided to the experts, and by applying their expert opinions, corrections were made and the formal and content validity was confirmed.Research findingsIn this research, by using covariance and correlation between independent and dependent variables, loading factors and variances of hidden variables can be estimated, and it can be used for confirmatory factor analysis and also structural equation modeling (casual construction with hidden variables), and the results of the factor loadings of the research variables were presented in the form of graphs. Values ​​of factor loadings greater than 0.7 were kept and the rest (q3, q5 and q9) were removed. The results showed the alignment of the questionnaire questions (except for the aforementioned indicators) to measure the concepts. The above results showed that the relationships between constructs or hidden variables can be cited. At the end, q5, q3, q9 indicators (because all their indicators have a factor load of less than 0.7) were removed and the modified model in the form of a diagram (1 and 2) was re-implemented.Evaluation criteria of the measurement model (outer model)With the help of Average Variance Extracted (AVE) index, it was found that all the studied constructs have an extracted average variance higher than 0.5; that is, the validity of the divergence of the research variables is confirmed. Combined reliability indices (CR), Cronbach's alpha and Rho coefficient are used to check the reliability of the questionnaire, and it is necessary to confirm the reliability of these indices higher than 0.7. All these coefficients are higher than 0.7 and show the reliability of the measurement tool.Divergent validity is a measure of the fit of measurement patterns and is checked through the HTMT coefficient. According to the researchers, this coefficient is the most reliable way to comment on the divergent validity, and it is based on the Monte Carlo simulation method. If this coefficient is below 0.9, there is divergent validity between the two constructs.Evaluation of structural model criteria (inner model)With the path coefficient of 0.886 and also the t-statistic of 25.539 obtained from the partial least squares method; at the 99% confidence level (given that the t-statistic is more than 2.57), structural factors are one of the factors of maintaining human resources.Discussion and conclusionIn explaining these findings, it can be said that job satisfaction is the result of a wide range of factors and elements that are effective on the quality of work life, and can even play a role as an independent factor in maintaining expert human resources. Existence of rich jobs with a meaningful and challenging and independent identity and nature with multiple tasks and responsibilities, leadership and management style based on value systems, trust in employees, conflict of opinions in decision-making and strategic areas, a dynamic, active and growing environment and the supporter of the elites and the culture of the organization in which they prominently witness the rule of transcendent social values, values ​​that have become social norms and are practically seen in the behavior and style of most social agents, some of which include central justice instead of unfair discrimination, criteria-based instead of relationalism, merit selection instead of dynasticism and work politics, etc., providing such a social environment helps to feel safe and calm, and experiencing such an environment will be the basis for the permanence of the organization's elites.According to the results of the research, it is suggested that the extraordinary payment of operational and war zones for specialist employees working in border and underprivileged areas should be put on the agenda in the seventh development plan. It is suggested that the duration of the official trial period of Article 46 be reduced from three years to two or one year in case of employment in the target areas.